Cycling time trial performance 4 hours after glycogen-lowering exercise is similarly enhanced by recovery nondairy chocolate beverages versus chocolate milk - Upshaw, A. U.; Wong, T. S.; Bandegan, A.; Lemon, P. W. R. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
Postexercise chocolate milk ingestion has been shown to enhance both glycogen resynthesis and subsequent exercise performance. To assess whether nondairy chocolate beverage ingestion post-glycogen-lowering exercise can enhance 20-km cycling time trial performance 4 hr later, eight healthy trained male cyclists (21.8 ± 2.3y, VO2max = 61.2 ± 1.4 ml·kg-1·min-1; M ± SD) completed a series of intense cycling intervals designed to lower muscle glycogen (Jentjens & Jeukendrup, 2003) followed by 4 hr of recovery and a subsequent 20-km cycling time trial. During the first 2 hr of recovery, participants ingested chocolate dairy milk (DAIRYCHOC), chocolate soy beverage (SOYCHOC), chocolate hemp beverage (HEMPCHOC), low-fat dairy milk (MILK), or a low-energy artificially sweetened, flavored beverage (PLACEBO) at 30-min intervals in a double-blind, counterbalanced repeated-measures design. All drinks, except the PLACEBO (247 kJ) were isoenergetic (2,107 kJ), and all chocolate-flavored drinks provided 1-g CHO·kg body mass-1·h-1. Fluid intake across treatments was equalized (2,262 ± 148 ml) by ingesting appropriate quantities of water based on drink intake. The CHO:PRO ratio was 4:1, 1.5:1, 4:1, and 6:1 for DAIRYCHOC, MILK, SOYCHOC, and HEMPCHOC, respectively. One-way analysis of variance with repeated measures showed time trial performance (DAIRYCHOC = 34.58 ± 2.5 min, SOYCHOC = 34.83 ± 2.2 min, HEMPCHOC = 34.88 ± 1.1 min, MILK = 34.47 ± 1.7 min) was enhanced similarly vs PLACEBO (37.85 ± 2.1) for all treatments (p = .019) These data suggest that postexercise macronutrient and total energy intake are more important for same-day 20-km cycling time trial performance after glycogen-lowering exercise than protein type or protein-to-carbohydrate ratio.